2022
DOI: 10.1177/09610006211070282
|View full text |Cite
|
Sign up to set email alerts
|

Research data management systems and the organization of universities and research institutes: A systematic literature review

Abstract: New technological developments, the availability of big data, and the creation of research platforms open a variety of opportunities to generate, store, and analyze research data. To ensure the sustainable handling of research data, the European Commission as well as scientific commissions have recently highlighted the importance of implementing a research data management system (RDMS) in higher education institutes (HEI) which combines technical as well as organizational solutions. A deep understanding of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 128 publications
(258 reference statements)
0
7
0
1
Order By: Relevance
“…Support for RDM requires expertise from multiple domains related to digital research infrastructure (Donner 2022). With a collaborative approach as our guiding principle and a focus on establishing a small, but agile, team, it is vital for Digital Research Services to connect and leverage resources and support from existing units within the university.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Support for RDM requires expertise from multiple domains related to digital research infrastructure (Donner 2022). With a collaborative approach as our guiding principle and a focus on establishing a small, but agile, team, it is vital for Digital Research Services to connect and leverage resources and support from existing units within the university.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent study by Jackson (2018) finds that research ethics boards (REBs) in the Canadian context, which are functionally equivalent to Institutional Review Boards (IRBs) in the US context, would welcome collaboration on knowledge transfer from the library regarding keeping up to date on cybersecurity or other RDM-related issues. Another recent systematic review of RDM at the organization level by Donner (2022) revealed that RDM is typically viewed from a strategic perspective as a multistakeholder endeavour, but legal expertise is often a missing piece.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Contoh best practice implementasi MDP di Amerika Serikat dan Kanada mereka banyak memberikan kesempatan pelatihan, konferensi dan lokakarya, untuk pustakawan dalam memberikan layanan MDP. Di Eropa, pustakawan banyak melakukan pengembangan keterampilan yang dibutuhkan melalui kursus pengembangan profesional, diikuti dengan mengintegrasikan manajemen data ke dalam kursus pelatihan profesional, dan mengikuti literatur praktis dan penyusunan pedoman (Donner, 2022). Sinergitas menjadi kata kunci utama dalam rangka peningkatan lingkungan yang mendukung MDP di Indonesia.…”
Section: Faktor Lingkunganunclassified
“…For instance, a person who experiences this may feel they do not have enough time in the day to "respond to the amount of digital data they receive" (p.2), or they may have a negative attitude toward ICT because they lack the knowledge or skills to use the equipment. Donner's (2022) research explored factors that are needed to successfully implement research data management (RDM) in HEI. They emphasise that if institutions are to utilise new technology, there is an increased need for "organizational solutions such as the development of support services" and to "develop and maintain an adequate IT infrastructure" (p.1).…”
Section: Teachers and Technologymentioning
confidence: 99%